The Effect of KATP Channel Blocker Glibenclamide on CGRP-Induced Headache and Hemodynamic in Healthy Volunteers - Coskun, Hande; Elbahi, Fatima Azzahra; Al-Karagholi, Mohammad Al-Mahdi; Ghanizada, Hashmat; Sheykhzade, Majid; Ashina, Messoud (Frontiers in Physiology, 2021)
Background: Calcitonin gene-related peptide (CGRP) dilates cranial arteries and triggers headache. The CGRP signaling pathway is partly dependent on activation of ATP-sensitive potassium (KATP) channels. Here, we investigated the effect of the KATP channel blocker glibenclamide on CGRP-induced headache and vascular changes in healthy volunteers. Methods: In a randomized, double-blinded, placebo-controlled, cross-over study, 20 healthy volunteers aged 18–27 years were randomly allocated to receive an intravenous infusion of 1.5 µg/min CGRP after oral pretreatment with glibenclamide (glibenclamide-CGRP day) or placebo (placebo-CGRP day). The primary endpoints were the difference in incidence of headache and the difference in area under the curve (AUC) for headache intensity scores (0–14 hours) between glibenclamide and placebo. The secondary endpoints were the difference in AUC for middle cerebral artery blood flow velocity (VMCA), superficial temporal artery (STA) and radial artery (RA) diameter, facial flushing, heart rate (HR) and mean arterial blood pressure (MAP) (0-4 hours) between glibenclamide and placebo. Results: We found no significant difference in the incidence of headache between glibenclamide-CGRP day (14/20, 70%) and placebo-CGRP day (19/20, 95%) (P=0.06). The AUC for headache intensity, VMCA, STA, RA, facial skin blood flow, HR and MAP did not differ between glibenclamide-CGRP day compared to placebo-CGRP day (P > 0.05). Conclusion: Pretreatment with a non-selective KATP channel inhibitor glibenclamide did not attenuate CGRP-induced headache and hemodynamic changes in healthy volunteers. We suggest that CGRP-induced responses could be mediated via activation of specific isoforms of sulfonylurea receptor subunits of KATP channel.